The Museum and The Drama: The Experience of the Object as Intercultural Education - Li, Xinlu (Trinity College (Dublin, Ireland). School of Education, 2022)
Drama-in-education can create an “in-between” time and space for audiences to explore the past in the immediacy of the present moment. The main role of a museum is to preserve the past in the present moment for future generations. The crossing points established in this thesis illuminate the potential for an intercultural and interactive education program, encompassing the interdisciplinarity of drama-in-education and museum studies to do so. This thesis ultimately aims to provide a praxis framework for drama in intercultural education. It does so by working with objects in a museum. The aim of incorporating drama-in-education methods into a museum education program is to create an embodied and imaginative learning environment. Engaging with an object as a pretext or stimulus enables an audience to live through a “moment” or moments, bringing an immediacy to life through history. Specifically, this thesis retraces interaction between the West and the East, through the history of the Bender’s collection in the National Museum of Ireland. Doing so opens up fresh perspectives on both the fascinating history of Irish American collectors such as Albert Bender and their passion for Asian artefacts. My research seeks to construct an effective intercultural and interdisciplinary learning framework for the National Museum of Ireland in the form of an art-based resource pack. In particular, I, the author, will focus on how visitors can understand this unique Asian collection, indigenous to my own Chinese culture.
Keywords: Drama in Education; Education